A sodium supplement material, anode electrode sheet and sodium battery

By accommodating the sodium wire in the polymer tube to form a sodium supplementary material with a core-shell structure, the problem of active Na+ loss in sodium ion batteries is solved, the energy density and cycle stability of the battery are improved, the service life is extended, and the production safety and operability are improved.

CN117117104BActive Publication Date: 2025-04-08BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210528475.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-16
Publication Date
2025-04-08
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

During the first charge and discharge process of sodium ion batteries, some active Na+ forms a solid electrolyte interface mask (SEI) at the negative electrode, resulting in a loss of battery capacity and shortening of service life. The existing sodium supplementation method has safety hazards and cycle stability problems.

Method used

By accommodating the sodium wire in the polymer tube, a sodium replenishing material with a core-shell structure is formed. The water- and oxygen-retaining properties of the polymer tube are steadily provided to avoid excessive loss of active Na+.

Benefits of technology

It improves the energy density and cycle stability of sodium batteries, extends the service life of the battery, and at the same time enhances production safety and process operability, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003645572310000131
    Figure BDA0003645572310000131
Patent Text Reader

Abstract

The present application provides a sodium supplement material, a negative electrode plate and a sodium battery, wherein the sodium supplement material comprises a polymer tube and a sodium metal wire contained in the polymer tube. The sodium metal wire is contained in the polymer tube, has good storage stability, and is easily dispersed evenly during the preparation of the negative electrode active material and the battery, so that the preparation process of the sodium battery is highly operable, highly safe and has low process costs. The negative electrode plate containing the above-mentioned sodium supplement material can be used to provide a sodium battery with a higher first coulomb efficiency, a higher energy density, better cycle stability and a longer cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a sodium supplement material, a negative electrode sheet and a sodium battery. Background Art

[0002] At present, sodium-ion batteries have the advantages of low cost, high safety, and fast charging capability, but the energy density of sodium-ion batteries is not as good as that of lithium-ion batteries. During the first charge and discharge process of sodium-ion batteries, some active Na + A solid electrolyte interface (SEI) will be formed at the negative electrode, making the overall active Na + The number is significantly reduced, and the capacity and performance of the electrode active materials cannot be fully utilized, resulting in the loss of battery capacity and shortened battery life. At present, the industry often solves the above problems by supplementing sodium in the negative electrode. The industry generally directly mixes elemental sodium or sodium phosphide coated with a protective layer into the negative electrode active material for sodium supplementation. Both of the above methods have certain disadvantages: for example, elemental sodium is highly active, the production conditions are harsh, and it is easy to cause production safety accidents; sodium phosphide materials will trigger some side reactions after decomposition, affecting the cycle stability of the battery. Summary of the invention

[0003] In view of this, the present application provides a sodium supplement material, a negative electrode plate and a sodium battery. The sodium metal wire is contained in a polymer tube, has good storage stability, and is easy to be evenly dispersed during the preparation of the negative electrode active material and the battery, so that the preparation process of the sodium battery is highly operable, safe and has low process cost.

[0004] Specifically, the first aspect of the present application provides a sodium supplement material, which includes a polymer tube and a sodium metal wire accommodated in the polymer tube.

[0005] Placing the sodium metal wire in a polymer tube can protect the sodium metal wire from damage by air and moisture, thereby improving the storage stability of the sodium supplement material. In addition, the filamentous sodium supplement material has good dispersibility, which can avoid the dispersion difficulties and easy agglomeration of traditional powdered and granular sodium supplement materials. Moreover, the core-shell structure of the sodium supplement material also enables it to exert excellent water and oxygen isolation properties in the subsequent pulping and preparation of pole pieces, thereby improving production safety and the operability of the battery preparation process, which is beneficial to reduce production costs. In addition, the polymer tube can provide a relatively stable external support for the sodium metal wire, which can effectively prevent a large amount of active Na in the sodium supplement material from being released during battery operation. + The sodium metal wire is detached from both ends of the polymer tube, and its volume becomes smaller, causing the negative electrode current collector to be exposed and sodium to precipitate on the exposed current collector surface, thereby improving the structural stability of the battery and facilitating the normal performance of the battery.

[0006] In some embodiments of the present application, the diameter d1 of the sodium metal wire is in the range of 0.3-1.8 mm. In some specific embodiments, the diameter d1 of the sodium metal wire is in the range of 0.5-1.7 mm. Exemplarily, the diameter d1 of the sodium metal wire can be 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, etc.

[0007] In some embodiments of the present application, the outer diameter d2 of the polymer tube is in the range of 0.5 mm to 2 mm. In some specific embodiments, the outer diameter d2 of the polymer tube is in the range of 0.9 mm to 1.5 mm. Exemplarily, the outer diameter d2 of the polymer tube can be 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2 mm, etc.

[0008] In some embodiments of the present application, the wall thickness of the polymer tube is in the range of 0.1 mm to 0.85 mm. In some specific embodiments, the wall thickness d3 of the polymer tube is in the range of 0.15 mm to 0.5 mm. Exemplarily, the wall thickness d3 of the polymer tube can be 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, etc.

[0009] Controlling the radial dimensions of the sodium supplement material within the above range is conducive to the uniform dispersion of the sodium supplement material in the negative electrode active material and making the active Na + Controlling the wall thickness of the polymer tube within a reasonable range is also conducive to ensuring that the polymer tube has a certain strength, so that it is not easy to be squeezed and deformed during the rolling process of the negative electrode sheet preparation, and it can also be used in a large number of active Na + After being removed, it maintains its original structural form.

[0010] In some embodiments of the present application, the diameter d1 of the sodium metal wire and the inner diameter d3 of the polymer tube satisfy: d1≤d3. In some specific embodiments, the diameter of the sodium metal wire is equal to the inner diameter of the polymer tube, that is, the lumen of the polymer tube is completely filled with sodium metal. If the sodium metal wire needs to be placed in the polymer tube, the radial dimensions of the two need to satisfy the above quantitative relationship.

[0011] In some embodiments of the present application, the relationship between the length L of the polymer tube and the outer diameter of the polymer tube satisfies: 10d2≤L≤40d2. In some specific embodiments, the relationship between the length L of the polymer tube and the outer diameter of the polymer tube satisfies: 20d2≤L≤30d2. Exemplarily, the length L of the polymer tube can be equal to 10d2, 15d2, 20d2, 25d2, 30d2, 35d2, 40d2, etc. Controlling the aspect ratio of the sodium supplement material polymer tube within the above range is beneficial to the uniform dispersion of the sodium supplement material in the negative electrode active material, and is also beneficial to the active Na + In addition, during the preparation of the negative electrode sheet, the sodium supplement materials with the above aspect ratio can be intertwined and entangled with each other to form a three-dimensional network structure, thereby further improving the structural stability of the sodium supplement materials during battery operation.

[0012] In some embodiments of the present application, the length of the sodium metal wire is consistent with the length of the polymer tube. In this case, the two ends of the sodium metal wire are completely flush with the two ends of the polymer tube, which is more conducive to the Na + Get out of the sodium supplement material.

[0013] In some embodiments of the present application, the material of the sodium metal wire includes at least one of sodium and a sodium alloy. The alloying elements in the sodium alloy include at least one of Mg, B, Al, Sn, Ge, Si, Pb, Ag, In, Zn, Ga and P. The sodium metal wire may be sodium, or an intermetallic compound formed by sodium and other elements, or a mixture of sodium and the intermetallic compound, or a simple mixture of sodium and other elements.

[0014] In some embodiments of the present application, the mass fraction of the sodium metal wire in the sodium supplement material is in the range of 1%-80%. In some specific embodiments, the mass fraction of the sodium metal wire in the sodium supplement material is in the range of 30%-50%. Exemplarily, the mass fraction of the sodium metal wire in the sodium supplement material can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc. The mass percentage of the sodium metal wire in the sodium supplement material can be controlled by controlling the wall thickness and outer diameter of the polymer tube. By controlling the mass percentage of the sodium metal wire within the above range, the amount of sodium supplement and the structural strength of the sodium supplement material can be taken into account, and at the same time, the proportion of negative active materials in the negative electrode sheet can be controlled to be high.

[0015] In some embodiments of the present application, the material of the polymer tube includes but is not limited to at least one of polytetrafluoroethylene (PTFE), polydimethylsiloxane (PDMS), polyethylene oxide (PEO) and styrene-butadiene rubber (SBR). The polymer has certain strength and chemical resistance, can provide certain structural strength for the sodium supplement material, and can stably exist in the battery while providing protection for the sodium metal wire, and will not affect the performance of the battery.

[0016] In some embodiments of the present application, the outer wall of the polymer tube is coated with a conductive layer. In some specific embodiments, the material of the conductive layer includes but is not limited to at least one of acetylene black, carbon nanotubes, carbon fibers and carbon black. The conductive layer coated on the outer wall of the polymer tube can act as a conductive agent for the negative electrode, which can effectively solve the problem that the conductive agent is not easily dispersed when directly added to the negative electrode active material. In addition, an appropriate amount of conductive agent is beneficial to the performance of the battery.

[0017] In some embodiments of the present application, a carbonized layer is attached to the polymer tube. The carbonized layer is a carbonization product of the polymer tube. For example, an amorphous carbon layer is formed after the polytetrafluoroethylene polymer tube is carbonized. In this case, the sodium supplement material is a carbonized or partially carbonized polymer tube and a sodium metal wire contained in the carbonized or partially carbonized polymer tube. The carbide partially replaces the original polymer, so that the mass proportion of sodium metal in the sodium supplement material is improved to a certain extent. In the above case, in the preparation of the negative electrode plate, no additional conductive material may be added, or a small amount of conductive material may be added for supplementation, which can be selected according to actual production needs.

[0018] In some embodiments of the present application, the sodium-supplementing material is prepared by coaxial spinning. In some specific embodiments, the sodium-supplementing material is prepared by coaxial spinning: the spinning equipment includes two coaxial material cavities inside and outside and two coaxial nozzles inside and outside, wherein the inner material cavity contains molten sodium metal, the outer material cavity contains molten polymer, and the inner diameter of the outer cavity nozzle is greater than or equal to the outer diameter of the inner cavity nozzle. When the materials in the inner and outer material cavities are ejected at the same linear velocity, and after rapid cooling, forming, and wire collection, a continuous sodium-supplementing material can be obtained. In the above process, the diameter of the sodium-supplementing material can be controlled by adjusting the linear velocity of the material ejection, the linear velocity of the wire collection roller, and the diameter of the nozzle. The above product can also be cut according to actual production needs to obtain the sodium-supplementing material provided in the present application.

[0019] In other embodiments of the present application, the sodium-supplementing material is prepared by pouring molten sodium metal into a commercially available polymer tube. In some specific embodiments, in a glove box, a commercially available polymer tube that meets the requirements of the present application is immersed in molten sodium metal, and kept in a high-temperature vacuum furnace for a period of time, taken out and cooled, and after the sodium metal is solidified and formed, the sodium metal remaining on the outer wall of the polymer tube is removed to obtain the sodium-supplementing material provided by the present application.

[0020] The second aspect of the present application also provides a negative electrode plate, which contains the sodium supplement material provided in the first aspect of the present application. The negative electrode plate is evenly dispersed with sodium metal wires wrapped in polymer tubes as a sodium supplement source, which can stably supplement the active Na lost by forming the SEI film for the battery. + , thereby improving the battery's energy density and cycle stability and extending the battery's service life.

[0021] In some embodiments of the present application, the negative electrode plate includes a current collector, and a negative electrode active material layer is disposed on at least one side of the current collector, and the negative electrode active material layer contains the sodium supplement material and the negative electrode active material. The specific content of the sodium supplement material in the negative electrode active material layer can be determined according to actual production.

[0022] In this case, the preparation of the negative electrode sheet may include the following steps:

[0023] (1) placing the negative electrode active material and the aforementioned sodium supplement material in a mechanical stirrer, stirring and mixing under an inert atmosphere to obtain a negative electrode composite material;

[0024] (2) adding the above-mentioned negative electrode composite material, binder and optional conductive agent into a solvent, stirring evenly under a vacuum environment to obtain a negative electrode slurry;

[0025] (3) The negative electrode slurry is coated on a current collector, and then dried, rolled, and die-cut to obtain a negative electrode sheet.

[0026] The preparation method has simple process, strong operability, high production efficiency and high safety during the preparation process, and is suitable for large-scale industrial production.

[0027] In some embodiments of the present application, the negative electrode plate includes a current collector, and a negative electrode active material layer and a sodium supplement layer are sequentially arranged on at least one side surface of the current collector, the negative electrode active material layer is arranged close to the current collector, and the sodium supplement layer contains the sodium supplement material and a binder.

[0028] In this case, the preparation of the negative electrode sheet may include the following steps:

[0029] (1) adding a negative electrode active material, a binder and an optional conductive agent into a solvent, stirring and mixing under a vacuum environment to obtain a negative electrode slurry;

[0030] (2) adding the aforementioned sodium-supplementing material and the binder into a solvent, and stirring them evenly under a vacuum environment to obtain a sodium-supplementing composite material;

[0031] (3) The negative electrode slurry and the sodium-supplementing composite material are sequentially coated on a current collector, and dried, rolled, and die-cut to obtain a negative electrode sheet; wherein the negative electrode sheet comprises a current collector, and a negative electrode active material layer and a sodium-supplementing layer are sequentially disposed on at least one side of the current collector.

[0032] The preparation method has simple process, strong operability, high production efficiency and high safety during the preparation process, and is suitable for large-scale industrial production.

[0033] In some embodiments of the present application, the negative electrode sheet contains a three-dimensional network formed by the sodium supplement material. The three-dimensional network is formed by a plurality of filamentous sodium supplement materials interlaced. The three-dimensional network can be located in the negative electrode active material layer or in the sodium supplement layer alone. The three-dimensional network has better structural stability and can stably provide active Na for the battery. + .

[0034] In some embodiments of the present application, the above-mentioned binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin (such as polyethylene, polypropylene, polystyrene, etc.), sodium carboxymethyl cellulose (CMC) and sodium alginate.

[0035] In some embodiments of the present application, the negative electrode active material may be a material known to those skilled in the art. For example, the negative electrode active material may be graphene, hard carbon, soft carbon, carbon nanotubes, metal alloy materials, and the like.

[0036] In some embodiments of the present application, the current collector includes, but is not limited to, copper foil or aluminum foil.

[0037] In some embodiments of the present application, the conductive agent is a material well-known to those skilled in the art. Exemplarily, the conductive agent may be carbon nanotubes (CNT), carbon fiber conductive agent (HV), carbon black (such as acetylene black, Ketjen black), furnace black, graphene, etc.

[0038] In some embodiments of the present application, the preparation of the negative electrode sheet further includes step (4): welding a tab on the wide side of the negative electrode sheet.

[0039] The third aspect of the present application provides a sodium battery, which is equipped with the negative electrode sheet provided by the second aspect of the present application. This sodium battery has a high initial Coulomb efficiency, a high energy density, good cycle stability, and a long cycle service life.

[0040] In some embodiments of the present application, the provided negative electrode sheet, a conventional separator in the art, and a positive electrode sheet are stacked in sequence to obtain a dry battery cell, and then subsequent processes are carried out to prepare a soft-pack and / or hard-shell battery.

[0041] In some other embodiments of the present application, the provided negative electrode sheet, a conventional separator in the art, and a positive electrode sheet are wound to obtain a dry battery cell, and then subsequent processes are carried out to prepare a soft-pack and / or hard-shell battery.

[0042] In some embodiments of the present application, the positive electrode sheet includes a positive current collector and a positive active material, and the positive active material is a conventional positive active material in the art. Exemplarily, the positive active material includes, but is not limited to, two-dimensional layered transition metal compounds (for example, NaM1 x M2 y M3 z O2, where M1, M2, and M3 each independently include at least one of Ni, Co, Mn, Fe, Cu, Mg, Ti, Al, Li, and Zn, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1), transition metal phosphates, Prussian blue-based materials, and polyanion materials. Detailed Embodiments

[0043] The technical solution of the present application will be described in detail below with reference to specific embodiments.

[0044] Example 1

[0045] (1) Preparation of sodium supplement material

[0046] A commercially available PTFE capillary with an outer diameter d2 of 0.6 mm, a wall thickness d3 of 0.15 mm, and a length L of 12 mm is immersed in molten sodium metal in a glove box protected by an argon atmosphere, and is placed in a high-temperature vacuum furnace at 190° C. for 30 minutes, so that the PTFE capillary is fully filled with sodium metal, that is, the diameter d1 of the sodium metal wire is 0.3 mm; then the PTFE capillary filled with sodium metal is taken out and cooled, and the residual sodium metal on the surface is cleaned to obtain the sodium supplement material provided in the embodiment of the present application. The diameter d1 of the sodium metal wire in the sodium supplement material is 0.3 mm, and the mass percentage of the sodium metal in the sodium supplement material is 13.31%.

[0047] (2) Preparation of negative electrode sheet

[0048] Weigh 910g of the negative electrode active material - hard carbon and a certain amount of the sodium supplement material obtained in step (1), stir and mix in a mechanical stirrer protected by argon atmosphere for 5h at a speed of 2000rpm / min to obtain a negative electrode composite material. Among them, the mass ratio of hard carbon to sodium metal wire is 95:5. Then the above-mentioned negative electrode composite material, binder - PVDF, conductive agent - acetylene black, carbon fiber conductive agent (HV) are added together to 2000g solvent N-methylpyrrolidone (NMP) so that the mass ratio of negative electrode composite material, PVDF, acetylene black, and HV is 96:3:0.5:0.5, and then stirred in a vacuum mixer to form a stable and uniform negative electrode slurry. The negative electrode slurry was evenly coated on both sides of the negative electrode current collector - aluminum foil (the width of the aluminum foil was 160 mm and the thickness was 8 μm) using a slit coating device, dried at 393 K, and pressed and die-cut by a roller press to obtain a rectangular sample with a size of 49 mm × 57 mm. The pole ears were spot welded on the wide sides of the sample to obtain the negative electrode sheet provided in the embodiment of the present application.

[0049] (3) Preparation of positive electrode sheet

[0050] 900g of the positive electrode active material - NaNi 0.4 Fe 0.2 Mn 0.4 O2 material, 50g of conductive agent-acetylene black, and 50g of adhesive-PVDF are added to 2000g of solvent-NMP, and then stirred in a vacuum mixer to form a stable and uniform positive electrode slurry. The positive electrode slurry is evenly and intermittently coated on both sides of the positive electrode current collector-aluminum foil (the width of the aluminum foil is 160mm and the thickness is 12μm) using a slit coating device, and dried at 393K. After rolling and die-cutting, a rectangular sample with a size of 48mm×56mm is obtained, and the upper ear is spot welded on the wide side of the sample to obtain a positive electrode sheet.

[0051] (4) Battery production

[0052] The negative electrode sheet obtained in step (2), the separator, and the positive electrode sheet obtained in step (3) are alternately stacked to obtain a dry battery cell. The positive and negative electrode sheets are alternately separated by the separator. The dry battery cell is placed in an aluminum-plastic film outer package, injected with electrolyte, and then vacuum-sealed. After being left at 60° C. for 48 hours, the sodium battery provided in this embodiment is obtained after pressurization, secondary packaging, exhaust, and capacity division at 60° C. This sodium battery is denoted as S1.

[0053] Example 2

[0054] The difference from Example 1 is that a PTFE capillary with an outer diameter d2 of 2 mm, a wall thickness d3 of 0.1 mm, and a length L of 80 mm is used to make the sodium supplement material. The diameter d1 of the sodium metal wire in the prepared sodium supplement material is 1.8 mm, and the mass percentage of the sodium metal element in the sodium supplement material is 66.3%. The prepared sodium battery is recorded as S2.

[0055] Example 3

[0056] The difference from Example 1 is that in step (1), the sodium-supplementing material is prepared by a coaxial spinning method. Specifically, the inner material cavity of the coaxial spinning device contains molten sodium metal, the outer material cavity contains molten PTFE, and the inner diameter of the outer cavity nozzle is larger than the outer diameter of the inner cavity nozzle. The materials in the inner and outer material cavities are ejected at the same linear velocity, and after rapid cooling, forming, wire collection and slitting, a sodium-supplementing material having an outer diameter d2 of 1 mm, a wall thickness d3 of 0.15 mm, and a length L of 25 mm is obtained. The diameter d1 of the sodium metal wire in the prepared sodium-supplementing material is 0.7 mm, and the mass percentage of the sodium metal in the sodium-supplementing material is 30.7%. The prepared sodium battery is recorded as S3.

[0057] Example 4

[0058] The difference from Example 1 is that in step (1), a commercially available PTFE capillary tube with an outer diameter d2 of 2 mm, a wall thickness d3 of 0.85 mm, and a length L of 20 mm is used to prepare the sodium supplement material. The diameter d1 of the sodium metal wire in the prepared sodium supplement material is 0.3 mm, and the mass percentage of the sodium metal element in the sodium supplement material is 1.0%. The prepared sodium battery is recorded as S4.

[0059] Example 5

[0060] The difference from Example 1 is that in step (1), a commercially available PTFE capillary tube with an outer diameter d2 of 0.5 mm, a wall thickness d3 of 0.1 mm, and a length L of 15 mm is used to prepare the sodium supplement material. The diameter d1 of the sodium metal wire in the prepared sodium supplement material is 0.3 mm, and the mass percentage of the sodium metal element in the sodium supplement material is 20.6%. The prepared sodium battery is denoted as S5.

[0061] Example 6

[0062] The difference from Example 1 is that in step (1), a commercially available PTFE capillary tube with an outer diameter d2 of 1 mm, a wall thickness d3 of 0.15 mm, and a length L of 50 mm is used to prepare the sodium supplement material. The diameter d1 of the sodium metal wire in the prepared sodium supplement material is 0.3 mm, and the mass percentage of the sodium metal element in the sodium supplement material is 30.7%. The prepared sodium battery is denoted as S6.

[0063] Example 7

[0064] The difference from Example 1 is that in step (1), a commercially available PTFE capillary tube with an outer diameter d2 of 2.2 mm, a wall thickness d3 of 1 mm, and a length L of 120 mm is used to prepare the sodium supplement material. The diameter d1 of the sodium metal wire in the prepared sodium supplement material is 0.2 mm, and the mass percentage of the sodium metal element in the sodium supplement material is 0.4%. The prepared sodium battery is denoted as S7.

[0065] Example 8

[0066] The difference from Example 1 is that in step (1), a carbon layer is also coated on the outer wall of the PTFE tube. The prepared sodium battery is denoted as S8.

[0067] Example 9

[0068] The difference from Example 1 is that in step (1), the PTFE tube used is a partially carbonized PTFE tube. The mass percentage of sodium metal element in the prepared sodium supplement material is 15.4%. The prepared sodium battery is denoted as S9.

[0069] Example 10

[0070] The difference from Example 1 is that in step (1), the inner material cavity of the coaxial spinning device contains molten sodium metal and the outer material cavity contains PDMS. The materials in the inner and outer material cavities are ejected at the same linear velocity, and quickly solidified and cooled to form, and then processed and cut to obtain a sodium-supplementing material having an outer diameter d2 of 0.6 mm, a wall thickness d3 of 0.15 mm, and a length L of 12 mm. The diameter d1 of the sodium metal wire in the obtained sodium-supplementing material is 0.3 mm, and the mass percentage of the sodium metal in the sodium-supplementing material is 20.3%. The obtained sodium battery is recorded as S10.

[0071] Embodiment 11

[0072] The difference from Example 1 is that in step (1), sodium metal is replaced by Na-Al alloy, and the Al content in the Na-Al alloy is 30%. Specifically, a commercially available PTFE capillary with an outer diameter d2 of 0.6 mm, a wall thickness d3 of 0.15 mm, and a length L of 12 mm is immersed in molten Na-Al alloy in a glove box protected by an argon atmosphere, and is vacuum-insulated at 205°C in a high-temperature vacuum furnace for 30 minutes. After the PTFE capillary is fully filled with Na-Al alloy, it is taken out and cooled, and the residual Na-Al alloy on the surface is cleaned to obtain the sodium supplement material provided in the embodiment of the present application. The diameter d1 of the sodium metal wire in the sodium supplement material is 0.3 mm, and the mass percentage of the Na-Al alloy in the sodium supplement material is 20.7%. The obtained sodium battery is recorded as S11.

[0073] Example 12

[0074] The difference from Example 1 is that in step (2), 910g of negative electrode active material-hard carbon, binder-PVDF, conductive agent-acetylene black, carbon fiber conductive agent (HV) are weighed and added to 2000g solvent N-methylpyrrolidone (NMP), and then stirred in a vacuum mixer to form a stable and uniform negative electrode slurry. The negative electrode slurry is evenly coated on both sides of the negative electrode current collector-aluminum foil (the width of the aluminum foil is 160mm and the thickness is 8μm) using a slit coating device; then the sodium supplement material and binder-PVDF prepared in Example 1 are added to NMP, stirred evenly in a vacuum mixer, and then coated on both sides of the aluminum foil with the negative electrode slurry, placed at 393K for drying, and rolled and die-cut to obtain a rectangular sample with a size of 49mm×57mm. The pole ears are spot welded on the wide side of the sample to obtain the negative electrode sheet provided in the embodiment of the present application. In the negative electrode sheet, the mass ratio of the negative electrode active material - hard carbon and sodium metal element is 95:5.

[0075] The prepared sodium battery is recorded as S12.

[0076] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0077] Comparative Example 1

[0078] (1) Preparation of negative electrode sheet

[0079] 910g of negative electrode active material-hard carbon, a certain amount of binder-PVDF, conductive agent-acetylene black and conductive agent-HV were added to 2000g solvent-NMP, and then stirred in a vacuum mixer to form a stable and uniform negative electrode slurry. In the negative electrode slurry, the negative electrode slurry was evenly coated on both sides of the negative electrode current collector-aluminum foil (the width of the aluminum foil was 160mm and the thickness was 8μm) using a slit coating device, placed at 393K for drying, and after rolling and die-cutting, a rectangular sample with a size of 49mm×57mm was obtained, and the upper tab was spot welded on the wide side of the sample to obtain a negative electrode sheet.

[0080] (2) Preparation of positive electrode sheet

[0081] 900g of the positive electrode active material - NaNi 0.4 Fe 0.2 Mn 0.4 O2 material, 50g of conductive agent-acetylene black, and 50g of adhesive-PVDF are added to 2000g of solvent-NMP, and then stirred in a vacuum mixer to form a stable and uniform positive electrode slurry. The positive electrode slurry is evenly and intermittently coated on both sides of the positive electrode current collector-aluminum foil (the width of the aluminum foil is 160mm and the thickness is 12μm) using a slit coating device, and dried at 393K. After rolling and die-cutting, a rectangular sample with a size of 48mm×56mm is obtained, and the upper pole ear is spot welded on the wide side of the sample to obtain a positive electrode sheet (same as in the embodiment).

[0082] (3) Battery production

[0083] The negative electrode sheet obtained in step (2), the separator, and the positive electrode sheet obtained in step (3) are alternately stacked to obtain a dry battery cell. The positive and negative electrode sheets are alternately separated by the separator. The dry battery cell is placed in an aluminum-plastic film outer package, injected with electrolyte, and then vacuum-sealed. After being left at 60° C. for 48 hours, a sodium battery is obtained after pressurization at 60° C., secondary packaging, exhaust, and capacity division. The sodium battery is recorded as DS1.

[0084] Comparative Example 2

[0085] The difference from Example 1 is that the sodium supplement material used is commercially available sodium phosphide powder. 910g of the negative electrode active material - hard carbon and a certain amount of sodium phosphide were weighed, and stirred and mixed in a mechanical stirrer protected by argon atmosphere for 5 hours at a speed of 2000rpm / min to obtain a negative electrode composite material, wherein the mass ratio of hard carbon to sodium phosphide is 95:5; then the above-mentioned negative electrode composite material, binder - PVDF, conductive agent - acetylene black, and carbon fiber conductive agent (HV) were added together to 2000g solvent - NMP, and then stirred in a vacuum stirrer to form a stable and uniform negative electrode slurry; in the negative electrode slurry, the mass ratio of the above-mentioned negative electrode composite material, PVDF, acetylene black and HV was 96:3:0.5:0.5. The negative electrode slurry was evenly coated on both sides of the negative electrode current collector - aluminum foil (the width of the aluminum foil was 160 mm and the thickness was 8 μm) using a slit coating device, dried at 393 K, and rolled and die-cut to obtain rectangular samples with a size of 49 mm × 57 mm. The pole ears were spot welded on the wide sides of the samples to obtain negative electrode sheets.

[0086] The same steps as those in Comparative Example 1 were used to assemble the negative electrode sheet prepared above and the positive electrode sheet prepared in Comparative Example 1 into a sodium battery, and the prepared sodium battery was recorded as DS2.

[0087] After the batteries prepared in the above-mentioned embodiments 1-12 and comparative examples 1-2 were formed respectively, they were subjected to charge and discharge cycle tests: on the LAND CT 2001C secondary battery performance test device, under the condition of 25±1°C, the batteries were subjected to charge and discharge cycle tests at 0.2C. The steps are as follows: leave for 10 minutes; charge at a constant voltage until 4.0V / 0.05C is cut off; leave for 10 minutes; discharge at a constant current until 1.0V is one cycle. Repeat this step. When the battery capacity is lower than 80% of the initial discharge capacity during the cycle, the cycle is terminated. The number of cycles is the cycle life of the battery. Five batteries were selected for each embodiment and comparative example for testing. The average value of the five batteries was taken for each group of test results. The test results of each battery are summarized in Table 1.

[0088] Table 1 Summary of performance test results of batteries prepared in various embodiments and comparative examples

[0089]

[0090] It can be seen from the data in Table 1 that the sodium supplementation material provided in the embodiment of the present application can effectively improve the first coulomb efficiency of the battery and extend the cycle life of the battery. Although the battery of Comparative Example 2 has a higher first coulomb efficiency, the byproducts produced after the decomposition of sodium phosphide affect the cycle stability of the battery, resulting in a shorter cycle life of the battery DS2.

[0091] The above are exemplary embodiments of the present application. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A sodium supplement material, characterized in that: The sodium supplement material includes a polymer tube and a sodium metal wire contained in the polymer tube; The diameter d1 of the sodium metal wire is in the range of 0.3 mm to 1.8 mm, and the length L of the polymer tube and the outer diameter d2 of the polymer tube satisfy: 10d2≤L≤40d2.

2. The sodium supplement material according to claim 1, characterized in that The outer diameter d2 of the polymer tube is in the range of 0.5 mm to 2 mm, and the wall thickness d3 of the polymer tube is in the range of 0.1 mm to 0.85 mm.

3. The sodium supplement material according to claim 1, characterized in that The material of the sodium metal wire includes at least one of sodium element and sodium alloy; wherein the alloy elements in the sodium alloy include at least one of Mg, B, Al, Sn, Ge, Si, Pb, Ag, In, Zn, Ga and P elements.

4. The sodium supplement material according to claim 1, characterized in that The mass percentage of the sodium metal wire in the sodium supplement material is in the range of 1%-80%.

5. The sodium supplement material according to claim 1, characterized in that The outer wall of the polymer tube is coated with a conductive layer.

6. The sodium supplement material according to claim 1, characterized in that The polymer tube has a carbonized layer attached thereto.

7. The sodium supplement material according to any one of claims 1 to 6, characterized in that The material of the polymer tube includes at least one of polytetrafluoroethylene, polydimethylsiloxane, polyethylene oxide and styrene-butadiene rubber.

8. A negative electrode plate, characterized in that: The negative electrode plate contains the sodium supplement material according to any one of claims 1 to 7.

9. A sodium battery, characterized in that: The sodium battery is provided with the negative electrode sheet as claimed in claim 8.

Citation Information

Patent Citations

  • Method for supplementing lithium to lithium ion battery pole piece

    CN106410120A

  • Method for supplementing sodium ion battery with sodium and electrode sheet and battery obtained by preparation

    CN109478639A